PEMIKIRAN EKONOMI UMAR BIN KHATHTHAB TENTANG KEBIJAKAN FISKAL - Esti Alfiah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Economic Policy of Umar bin Khattab's on fiscal policy makes progress for Muslims. State income consists of various zakat as taxes, 1/5 of spoils of war, jizya, kharaj, and 'ursyu. Fund management from various sources of funds is well managed, specific, and responsibility by him. Umar did not walk alone set it, he founded a financial institution that is Baitul Mal denggan equipped department needed so that the economy remains stable. Umar's behavior which can be taken for example to become a leader in economic matters is deliberation, establishing departments as needed, prioritizing what is the main rights, issuing policies by looking at the welfare of others, caring for society, putting people in work in accordance with their fields, the economy is said to be stable if the income is small compared to expenditure.